Guidelines for supporting re-use of existing digital learning materials and methods in higher education - Judith Schoonenboom; Henk Sligte; Eja Kliphuis (Association for Learning Technology, 2009)
The literature on the re-use of learning materials has largely focused on the development of materials. This paper explores how re-use can be stimulated after learning materials have been developed and made available. We searched for and developed guidelines that support staff and/or management most frequently adopt in cases of (un)successful re-use of existing digital teaching and learning materials and methods by teachers in higher education. In a grounded theory approach, we collected existing guidelines from 11 literature studies, and developed new guidelines from 19 (mainly Dutch) case studies. Through constant comparison, we developed ‘low-level' guidelines, which were classified into high-level guidelines. Five high-level guidelines turned out to be robust when subjected to repeated comparison with the case studies. Further, this paper elaborates existing guidelines by showing specific elaborations of them in our case studies.